Los rituales funerarios, un acercamiento teórico y metodológico al estudio de las prácticas mortuorias y sus significados durante la fase Curridabat (300-800 d.C.) - Peytrequín Gómez, Jeffrey (2013)
This essay discusses the reaches of a specific theoretical approach, based on the perspective of the history as a narrative and the archaeology of action, with regard to the analysis of funeral contexts. The information is presented with the purpose of suggesting its application toward a specific study case of ritual practices in the Central Area of Costa Rica.